Variables Within a Household That Influence Quality-of-Life Outcomes for Individuals With Intellectual and Developmental Disabilities Living in the Community: Discovering the Gaps. (March 2014) - Francis, Grace Lucille; Blue-Banning, Martha; Turnbull, Rud
Individuals with intellectual and developmental disabilities (IDD) and their families face many important decisions as the individuals with IDD enter adulthood, including where to live. Although there are numerous housing options for individuals with IDD outside of institutions, there is a paucity of information available to inform them about how various characteristics of these settings can affect their quality of life. The purpose of this study was to determine key variables within a household that influence individual quality of life (QOL) of people with IDD living in community settings, thereby enabling these individuals and their families to make informed decisions regarding housing options available to them.